2003
DOI: 10.1309/uueplf2phyxqdjnq
|View full text |Cite
|
Sign up to set email alerts
|

Follicular Hyperplasia, Follicular Lysis, and Progressive Transformation of Germinal Centers

Abstract: We studied mantle B-cell and T-cell ingression in hyperplastic follicles (HFs), follicular lysis (FL), and progressive transformation of germinal centers (PTGC) in 19 paraffin-embedded, H&E-, bcl-2-, CD20-, and CD3-stained lymph nodes. We enumerated the T cells (CD3+) and mantle B cells (bcl-2+/CD3-) per 100 cells in 5 high-power fields of each entity (mean +/- SD). Compared with HF, FL had increased numbers of T cells migrating into germinal centers (39.8 +/- 10.0 vs 25.8 +/- 7.8; P < .0001). and a mild incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 0 publications
2
23
0
Order By: Relevance
“…One of the theories about the cause of that inward migration is believed to be due to the redistribution of the germinal center T cells and the loss of their preferential location near the FDCs in the light zone, which likely induces subsequent B-cell migration [25]. Although PTGC has been linked to nodular lymphocyte predominant Hodgkin lymphoma in a small subset of the cases, it is more commonly seen in association with reactive follicular hyperplasia representing part of the spectrum of the reactive changes, where it has been reported that up to 10% of reactive nodes with nonspecific lymphadenitis contain one or more areas of PTGC [26]. At the early stages of PTGC process, the FDC Fig.…”
Section: Fdcs In Progressive Transformation Of Germinal Centers and Fmentioning
confidence: 99%
“…One of the theories about the cause of that inward migration is believed to be due to the redistribution of the germinal center T cells and the loss of their preferential location near the FDCs in the light zone, which likely induces subsequent B-cell migration [25]. Although PTGC has been linked to nodular lymphocyte predominant Hodgkin lymphoma in a small subset of the cases, it is more commonly seen in association with reactive follicular hyperplasia representing part of the spectrum of the reactive changes, where it has been reported that up to 10% of reactive nodes with nonspecific lymphadenitis contain one or more areas of PTGC [26]. At the early stages of PTGC process, the FDC Fig.…”
Section: Fdcs In Progressive Transformation Of Germinal Centers and Fmentioning
confidence: 99%
“…It typically affects focal areas within reactive lymph nodes, although a "florid" form involving multiple sites within individual lymph nodes and/or multiple lymph nodes has been described afflicting young men [62]. Histologically PTGC is characterized by lymph nodes with large, well-defined nodules containing an excess of B cells [63,64]. Some studies have reported 10%-30% of PTGC patients with antecedent, concurrent, or subsequent HL, particularly NLPHL [65,66], while others have not demonstrated such a correlation [62].…”
Section: Differential Diagnosis Of Nlphl and Associated Disorders Promentioning
confidence: 99%
“…(iii) Progressive transformation of GC (PTGC). 8,10,11 The PTGC appeared as a A relatively large number of residual centrocytes, centroblasts and immunoblasts were present, in addition to small mantle zone lymphocytes. HE, x100 (Case 3).…”
Section: Pathological Findingsmentioning
confidence: 99%
“…1c). 8,10,11 (iv) Large nodules of mantle cells contained multiple small atrophic GC with increased vascularity (multiple GC pattern) (Fig. 1d).…”
Section: Pathological Findingsmentioning
confidence: 99%
See 1 more Smart Citation